A Comparative Analysis of Salinity and Nickel Tolerance of Tomato (Solanum lycopersicum L.). Issue 18 (11th October 2019) - Amjad, Muhammad; Ameen, Nuzhat; Murtaza, Behzad; Abbas, Ghulam; Imran, Muhammad; Naeem, Muhammad Asif; Bhutta, Waqas Manzoor; Zakir, Ali; Masood, Nasir; Jacobsen, Sven-Erik
ABSTRACT: An experiment was conducted in a randomized factorial design with three replicates to elucidate the comparative tolerance of tomato genotypes and hybrids against salinity (NaCl) and nickel (Ni) toxicity. Six tomato genotypes and two hybrids were exposed to different levels of NaCl (0, 75 and 150 mM) and Ni (0, 15 and 20 mg L −1 ) in hydroponics for 4 weeks. Increasing levels of NaCl and Ni significantly decreased the growth of all the genotypes. Cluster analysis for relative tolerance of the genotypes and hybrids showed that the genotype "Naqeeb" is the most tolerant whereas the genotype "Nadir" proved to be the most sensitive against both the NaCl and Ni-toxicity. Leaf tissues Na + and Ni concentration significantly increased by increasing NaCl and Ni levels in the growth medium with tolerant genotype "Naqeeb" showing the lowest and sensitive genotype "Nadir" with the highest concentration. Antagonistic relation between uptake of Na + and Ni was observed in all the genotypes and hybrids. Results revealed that tomato genotypes and hybrids shared the same defense mechanism against salinity and Ni-toxicity tolerance. The genotypes tolerant against one stress can be regarded as tolerant against other stress as well.